Development and evaluation of a leadership training program for public health emergency response: results from a Chinese study - Xu Yihua; Wu Jing; Xiang Hao; Wei Sheng; Wang Chongjian; Liu Li; Nie Shaofa (BMC, 2008)
Abstract Background Since the 9/11 attack and severe acute respiratory syndrome (SARS), the development of qualified and able public health leaders has become a new urgency in building the infrastructure needed to address public health emergencies. Although previous studies have reported that the training of individual leaders is an important approach, the systemic and scientific training model need further improvement and development. The purpose of this study was to develop, deliver, and evaluate a participatory leadership training program for emergency response. Methods Forty-one public health leaders (N = 41) from five provinces completed the entire emergency preparedness training program in China. The program was evaluated by anonymous questionnaires and semi-structured interviews held prior to training, immediately post-training and 12-month after training (Follow-up). Results The emergency preparedness training resulted in positive shifts in knowledge, self-assessment of skills for public health leaders. More than ninety-five percent of participants reported that the training model was scientific and feasible. Moreover, the response of participants in the program to the avian influenza outbreak, as well as the planned evaluations for this leadership training program, further demonstrated both the successful approaches and methods and the positive impact of this integrated leadership training initiative. Conclusion The emergency preparedness training program met its aims and objectives satisfactorily, and improved the emergency capability of public health leaders. This suggests that the leadership training model was effective and feasible in improving the emergency preparedness capability.